Remote assessment of reserve capacity of outburst alpine lakes - V. G. Konovalov; V. A. Rudakov (Лëд и снег, 2016)
Results of distant satellite sounding (the TERRA satellite) of high-mountainous areas and digital models SRTM 4.1 and ASTER DEM G2 of the same relief were used to calculate the following parameters of high-mountain dammed glacial lakes: area, depth, the water volume, excess of the dam above the water level. It is important for estimation of the water volume that can be dangerous for a break-through of a dammed lake. Formulas deduced to calculate the depth and volume of a lake for several sections of its area were tested and proposed. It is demonstrated that the regression equation V = Hmax × F, where Hmax is maximum depth of the lake, can be used as the parameterization of the formula «lake volume V equals the product of the area F on average depth D». More precise values of the coefficients a and b in the formula V = aFb were also obtained. Parameters and the water volumes of lakes were estimated for the river Gunt (right tributary of Pyanj River) basin. According to [28], there are 428 high-mountain lakes in this region with their total area ≥ 2500 m2. For basin Inflow of melted snow and glacier water caused by the rise of mean summer air temperatures in 1931–2015 was estimated for the lake Rivankul basin (the Pamir Mountains).